Δ9-THC and N-arachidonoyl glycine regulate BV-2 microglial morphology and cytokine release plasticity: implications for signaling at GPR18 - McHugh, Douglas; Roskowski, Daniel; Xie, Sisi; Bradshaw, Heather B. (Frontiers in Pharmacology, 2014)
Microglial cells are extremely plastic and undergo a variety of CNS-prompted shape changes relative to their location and current role. Signaling molecules from neurons also regulate microglial cytokine production. Neurons are known to employ the endogenous cannabinoid system to communicate with other cells of the CNS. N-arachidonoyl glycine (NAGly) and Δ9-tetrahydrocannabinol (Δ9-THC) signaling via GPR18 has been introduced as an important new target in microglial-neuronal communication. Our hypothesis is that endogenous NAGly-GPR18 signaling regulates phenotypic shape and cytokine production in microglia, and is mimicked by Δ9-THC in the BV-2 microglia model system. BV-2 microglia were exposed to NAGly and Δ9-THC or Vh for 12 hours, which resulted in significant differences in the cell morphologies expressed. Cannabidiol (CBD) was effective at antagonizing the effects of both NAGly and Δ9-THC. Using ELISA-based microarrays, BV-2 microglia were exposed to NAGly and Δ9-THC or Vh for 3 hours and the presence of 40 cytokines in the culture media quantified. Production of Axl, CD40, IGF-I, OPN and Pro-MMP-9 were significantly altered by NAGly and Δ9-THC, and antagonized by CBD. These data add to an emerging profile that emphasizes NAGly as a component of an endogenous system present in the CNS that tightly integrates microglial proliferation, recruitment and adhesion with neuron-glia interactivity and tissue remodeling.